2004
DOI: 10.1103/physrevd.70.024013
|View full text |Cite
|
Sign up to set email alerts
|

Making the hyper-Kähler structure ofN=2quantum string manifest

Abstract: We show that the Lorentz covariant formulation of Nϭ2 string in a curved space reveals an explicit hyper-Kähler structure. Apart from the metric, the superconformal currents couple to a background two-form. By superconformal symmetry the latter is constrained to be holomorphic and covariantly constant and allows one to construct three complex structures obeying a ͑pseudo͒quaternion algebra.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The superconformal structures exhibited in this paper are inspired by the wellknown supersymmetries of σ-models. Zumino [Zum79] and Alvarez-Gaumé and Freedman [AGF81] showed that nonlinear σ-models on general Riemannian, complex and hyperkähler targets carry N = 1, 2, 4 super-Poincaré symmetries, respectively (see [HKLR87,Fre99,IAS99] for excellent discussions, and [BGL04] for a related recent development). In the N = 2 case, this structure is superconformal when the target is Calabi-Yau.…”
Section: Introductionmentioning
confidence: 99%
“…The superconformal structures exhibited in this paper are inspired by the wellknown supersymmetries of σ-models. Zumino [Zum79] and Alvarez-Gaumé and Freedman [AGF81] showed that nonlinear σ-models on general Riemannian, complex and hyperkähler targets carry N = 1, 2, 4 super-Poincaré symmetries, respectively (see [HKLR87,Fre99,IAS99] for excellent discussions, and [BGL04] for a related recent development). In the N = 2 case, this structure is superconformal when the target is Calabi-Yau.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 5.1. Among conformally flat homogeneous non-locally symmetric fourdimensional pseudo-Riemannian non-trivial Ricci soliton with the Ricci operator of Segre types [22], [1,12] or [11,2], the Ricci Solitons examples are listed in the following Tables 3,4 and 5, where the checkmark means that X is invariant for all Lie algebras of that form. Proof.…”
Section: Cases With Degenerate Ricci Operator and Non-trivial Isotropymentioning
confidence: 99%
“…From now on, we fix an orthonormal basis {e 1 = x, e 2 = J x, e 3 , e 4 = J e 3 } for V such that y = (sinh ϕ 0 )J x + (cosh ϕ 0 )e 3 for some ϕ 0 . Taking the family of oriented nondegenerate mixed 2-planes π ϕ = {x, (sinh ϕ)J x + (cosh ϕ)e 3 } , a straightforward calculation from (4) shows that A(π ϕ ), when expressed with respect to the fixed orthornormal basis, takes the form…”
Section: Theorem 5 Let (V ) Be a Four-dimensional Inner Product Vec...mentioning
confidence: 99%
“…Pseudo-Riemannian metrics of signature other than Lorentzian have received considerable attention in mathematical physics since the work of Ooguri and Vafa [22] on N = 2 strings [4,8,17,19] to list but a few of the many possible references. Applications of pseudo-Riemannian metrics in braneworld cosmology have been discussed by Sahni and Shtanov [24].…”
Section: Introductionmentioning
confidence: 99%